Comparative economic value estimation of matsutake mushroom and timber production in Swedish Scots pine forest - Nagasaka, Kenji (SLU/Southern Swedish Forest Research Centre, 2013)
The economic value of Swedish forests is largely linked to the production of timber and pulp. Non-timber forest products such as berries and wild mushrooms have yet been considered commercially less valuable than what the trees produce. In 1990s, DNA analyses revealed that matsutake (Tricholoma matsutake), the most expensive edible wild mushroom in Japan, did also occur in Sweden. As a result, commercial matsutake picking in Sweden started in 1998 and since then, small scale export of it to Japan have been taken place. The main objective of this study is to estimate the economic value of Swedish matsutake in comparison with that of Scots pine timber production to figure out how matsutake could potentially contribute to forest management. Cost-benefit analysis is applied as a method. Regarding matsutake production, input data for calculating net present value (NPV) is collected from the matsutake sporocarp inventory survey conducted in between 1998-2012 and a questionnaire was sent to the pickers in 2013. Regarding timber production, state compensation payment for habitat protection that reflects the forest estate value is employed for estimating the NPV. The result shows that the economic values of matsutake at Scots pine sites with high sporocarp productivity is about twice as high as the economic outcome of timber production and it implies that the potential economic value production of matsutake sporocarps at high productivity sites may largely exceed the corresponding economic value of the timber production. This study also suggests that further researches on value estimations of recreational and subsistence use of matsutake and also resource tenure right of it are needed to clarify the cons and prons of forest management with consideration of potential matsutake sporocarp production.